Lean Management Implementation to Improve Productivity and Efficiency in Electrical Construction Projects: A Case Study at Bozer Construction Unipessoal LDA, Timor Leste - De Carvalho Belo, Gabriel Barreto (PT Inovasi Pratama Internasional, 2025)
This study aims to evaluate the implementation of Lean Management principles and their impact on productivity and efficiency in electrical construction projects, focusing on a case study at Bozer Construction Unipessoal LDA in Timor Leste.The research employs a qualitative descriptive method using a single embedded case study design. Data were collected through semi-structured interviews with key project staff, direct field observations, and analysis of internal project documentation.The study found that Lean tools—specifically Just-In-Time (JIT), Kaizen, and Total Quality Management (TQM)—significantly contributed to minimizing waste, improving scheduling accuracy, and enhancing workforce coordination. However, challenges were encountered, including limited knowledge of Lean concepts, cultural resistance to bottom-up improvement processes, and logistical barriers in maintaining timely material delivery.Despite constraints, the adoption of Lean strategies yielded measurable performance improvements: reduced project delays, enhanced material efficiency, and improved quality control. This case illustrates that Lean Management can be adapted effectively even in resource-constrained, post-conflict settings like Timor Leste.This study contributes to the limited empirical literature on Lean Construction in Southeast Asia, offering practical insights for similar developing country contexts. It demonstrates that local adaptation and incremental implementation of Lean principles can lead to substantial gains in project delivery performance